PENGEMBANGAN MEDIA SMART BOX (KOTAK PINTAR) DALAM PENGENALAN WARISAN BUDAYA INDONESIA KEPADA SISWA SANGGAR BELAJAR KEPONG MALAYSIA - Anjani, Namira; Kesuma Nasution, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objectives of this research include the design and development of Smart Box media to introduce Indonesian cultural heritage to students at Sanggar Belajar Kepong, Malaysia. The method used is Research and Development (R&D) with a 4D model approach, namely Define, Design, Develop, and Dissemination. This media is designed to increase students' interest and understanding of Indonesian culture. Data collection was carried out through validation and questionnaires involving 16 students. At the Define stage, student needs and learning objectives were identified. At the Design stage, the media concept and content were designed. At the Develop stage, the media was developed and tested. Finally, the Dissemination stage was carried out by introducing the media in learning activities. The results showed that the use of Smart Box significantly increased student engagement and provided an interactive learning experience. This media obtained a validity value of 95% from material experts, 94% from media experts, and 100% from teacher and student questionnaires, all of which were in the very valid category. The application of this systematic development model has been proven to be able to increase student participation and understanding of the material. Therefore, Smart Box is expected to be an effective solution in introducing Indonesian culture, especially in the context of education abroad.